Regional Disparities in Per Capita Income in India: Convergence or Divergence? - Rowan Cherodian; A. P. Thirlwall (University of Kent, School of Economics, 2013)
The paper looks at the latest evidence of what has been happening to regional disparities in per capita income (measured as Gross State Domestic Product per capita) in India over the first decade of the twenty first century (1999/00 to 2010/11) by estimating cross section equations for unconditional and conditional beta convergence and sigma convergence across thirty two regions (twenty-eight States and four Union Territories). There is no evidence of unconditional convergence, but weak evidence of conditional convergence controlling for population growth; credit growth; male literacy; the share of agriculture in State GDP, and State expenditure as a share of State GDP. Sigma divergence has increased continuously, except among the poorest States.
Keywords: O47; O53; R11; 330; Regional Growth; India; Convergence/Divergence